Matrix Metalloproteinases in Renal Diseases: A Critical Appraisal - Oskar Zakiyanov; Marta Kalousová; Tomáš Zima; Vladimír Tesař (Karger Publishers, 2019)
Matrix metalloproteinases (MMPs) are endopeptidases within the metzincin protein family that not only cleave extracellular matrix (ECM) components, but also process the non-ECM molecules, including various growth factors and their binding proteins. MMPs participate in cell to ECM interactions, and MMPs are known to be involved in cell proliferation mechanisms and most probably apoptosis. These proteinases are grouped into six classes: collagenases, gelatinases, stromelysins, matrilysins, membrane type MMPs, and other MMPs. Various mechanisms regulate the activity of MMPs, inhibition by tissue inhibitors of metalloproteinases being the most important. In the kidney, intrinsic glomerular cells and tubular epithelial cells synthesize several MMPs. The measurement of circulating MMPs can provide valuable information in patients with kidney diseases. They play an important role in many renal diseases, both acute and chronic. This review attempts to summarize the current knowledge of MMPs in the kidney and discusses recent data from patient and animal studies with reference to specific diseases. A better understanding of the MMPs' role in renal remodeling may open the way to new interventions favoring deleterious renal changes in a number of kidney diseases.